Efektifitas Fasilitas Jembatan Penyebrangan Terhadap Keselamatan Pejalan Kaki (Studi Kasus Manpower RDMP JPO Balikpapan) - M. Dendy Taferry, M. Dendy Taferry (aspal, 2024)
Abstrak. Pedestrian facilities are one aspect that has the potential to influence pedestrian safety. The high volume of pedestrian and vehicle traffic on Yos Sudarso Street, particularly in the area of Manpower RDMP JO, has led to the provision of a pedestrian overpass facilities for the Manpower RDMP JO. There are two pedestrian overpass facilities provided for the Manpower of RDMP JO, namely JPO 1 and JPO 2. This research aims to determine whether the pedestrian overpass complies with the standard guidelines of the Directorate General of Highways No. 027/T/Bt/1995, To determine the effectiveness level of pedestrian overpass based on pedestrian volume, and the relationship between pedestrian overpass facilities and pedestrian safety using the chi-square test method with SPSS. The method in this research uses a quantitative approach, based on the results of questionnaires, observations, and documentation. The research results indicate that the existing conditions of JPO 1 and JPO 2 meet the standards set forth in the guidelines for the planning of pedestrian overpasses, based on the standard guidelines from the Directorate General of Highways No. 027/T/Bt/1995. The effectiveness calculated based on the pedestrian volume obtained for each is JPO 1 at 59.9% (Fairly Effective) and JPO 2 at 69.9%. (Effective). From the chi-square test using SPSS, an asymptotic value of 0.00 was obtained. Which means that there is a relationship between variable X (crossing bridge facility) and variable Y ( Pedestrian Safety ). This can be interpreted that pedestrian overpass facilities have a significant impact on pedestrian safety.